STRATEGI PENGUMPULAN DANA UNTUK ZAKAT, INFAK DAN SODAKOH (ZIS) UNTUK PEMBERDAYAAN MASYARAKAT DI KABUPATEN BOGOR - Chandra Fitra Arifianto; Wahyu Nurul Faroh; Rahadyan Tajuddien; Ratnawati; Sri Eka Lestari (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2021)
This community service aims to provide a solution to the limitation of the movement of the Nahwa Nur Amil Zakat Institution (LAZ) in seeking potential Zakat, Infaq and Sodakoh (ZIS) funds during the Covid-19 pandemic. The materials were given online and then assistance was given to lighten the funding burden in ZIS management. LAZ Nahwa Nur personnel apparently still do not fully understand the fundraising strategy during the Covid-19 pandemic as it is today, even though they have used an online strategy using their own platform, it is still not optimal. So it is advisable to use an external platform that already exists in ZIS fundraising